2004
DOI: 10.1002/bies.20126
|View full text |Cite
|
Sign up to set email alerts
|

An intracellular actin motor in bacteria?

Abstract: Actin performs structural as well as motor-like functions in eukaryotic cells. Orthologues of actin have also been identified in bacteria, where they perform an essential function during cell growth. Bacterial actins are implicated in the maintenance of rod-shaped cell morphology, and appear to form a cytoskeletal structure, localising as helical filaments underneath the cell membrane. Recently, a plasmid-borne actin orthologue has been shown to perform a mitotic-like function during segregation of a plasmid, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…These experiments show that a decrease in the concentration of EF-Tu leads to a defect in cell morphology and in MreB localization, while translation is not detectably affected. In addition, MreB filaments did not show the dynamic turnover that characterizes MreB filaments in wild-type cells (13,14). We have shown that the dynamics of MreB filaments are essential for the proper function of the cytoskeletal element, indicating the need to ensure sufficient filament turnover (18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These experiments show that a decrease in the concentration of EF-Tu leads to a defect in cell morphology and in MreB localization, while translation is not detectably affected. In addition, MreB filaments did not show the dynamic turnover that characterizes MreB filaments in wild-type cells (13,14). We have shown that the dynamics of MreB filaments are essential for the proper function of the cytoskeletal element, indicating the need to ensure sufficient filament turnover (18).…”
Section: Discussionmentioning
confidence: 99%
“…These foci became most clearly visible during late exponential growth (OD 1.5-4) (Fig. 2C), and their pattern was somewhat reminiscent of the MreB cytoskeleton (12,14). Threedimensional deconvolution of Z stacks taken from cells bearing EF-Tu-CFP revealed an obvious punctuate or band-like distribution of EF-Tu ( Fig.…”
Section: Ef-tu Colocalizes and Interacts With Mreb In Helical Filamentsmentioning
confidence: 92%
See 1 more Smart Citation
“…A disputed question is the effect MreB exerts on the segregation of duplicated chromosomes. Interfering with MreB levels or polymerization activity has been shown to strongly impair chromosome segregation in several organisms [10],[17], but arguments against a direct involvement of MreB in segregation have also been put forward [18].…”
Section: Introductionmentioning
confidence: 99%
“…With the discovery that bacteria contain structural homologs of eukaryotic actin and tubulin (1,2), it was proposed that these polymers might have organizational and structural roles similar to their eukaryotic counterparts (3,4).…”
mentioning
confidence: 99%